Survival Skills in Digital Era: An Integration of Digital Literacy into EFL Classroom - Alfia, Nurul; Sumardi, Sumardi; Kristina, Diah (Indonesian Journal of EFL and Linguistics, 2020)
The development of digital technology has made digital natives encounter situations that require survival skills to face intense competition in the digital age. This case study investigates how students integrate their digital literacy in the EFL classroom and what components of digital literacy are frequently integrated by the students. Three students from a senior high school in Surakarta were recruited purposively. A case study design was used in this research study. The results of interviews and observations revealed that in practice, students integrate digital literacy in every activity related to the use of the internet and digital tools. Students tended to integrate digital literacy according to the activity and objective to be achieved, ranging from searching for and understanding information to make new products. Meanwhile, digital literacy frequently integrated by the students was photo-visual literacy, information literacy, reproduction literacy, and real-time thinking literacy.